Melittin: A Natural Component of Honeybee Venom as a Potential Anti-Cancer Therapy - Niamh Donnellan; Anne M Friel (SURE Journal: (Science Undergraduate Research Experience Journal))
Cancer is a major cause of death worldwide and while chemotherapy is the main approach there are many negative associations in current treatment procedures. These include lack of selectivity, side effects and drug resistance. The hallmarks of cancer are a fundamental concept which aids the development of new means to treat human cancers through the understanding of the acquisition of these hallmarks from cells. Melittin is a major peptide component of bee venom which has shown to be efficacious as an anticancer agent in preclinical and animal models. Melittin has many biological functions including pore formation in the phospholipid bilayer causing cell permeability and lysis. It interacts with various biological signalling pathways which suppress tumour cells, notably, the Hypoxia-Inducible Factor-1, Vascular Endothelial Growth Factor and the Nuclear Factor Kappa B pathways. Despite convincing data presented, its pertinency to human studies has been met with challenges due to non-specific cytotoxicity and haemolytic capabilities. Optimisation techniques for melittin have been developed including the use of gene therapy, co-delivery and nanoparticles. Melittin’s biological functions, the potential methods of delivery and current trends in melittin development for therapy are presented and discussed in this review.